Enhancement of the X-Arapuca photon detection device for the DUNE experiment. (22nd September 2021) - Brizzolari, C.; Brovelli, S.; Bruni, F.; Carniti, P.; Cattadori, C.M.; Falcone, A.; Gotti, C.; Machado, A.A.; Meinardi, F.; Pessina, G.; Segreto, E.; Souza, H.V.; et al.
Abstract: In the Deep Underground Neutrino Experiment (DUNE), the VUV LAr luminescence is collected by light trap devices named X-Arapuca, sizing ∼ (480 × 93) mm 2 . Six thousand of these units will be deployed in the first DUNE ten kiloton far detector module. In this work we present the first characterisation of the photon detection efficiency of an X-Arapuca device sizing ∼(200 × 75) mm 2 via a complete and accurate set of measurements along the cell longitudinal axis with a movable 241 Am source. The MPPCs photosensors are readout by a cryogenic trans-impedance amplifier to enhance the single photoelectron sensitivity and improve the signal-to-noise while ganging 8 MPPC for a total surface of 288 mm 2 . Moreover, we developed a new photon downshifting polymeric material, by which the X-Arapuca photon detection efficiency was enhanced of about +50% with respect to the baseline off-shell product deployed in the standard device configuration. The achieved results are compared to previous measurements on a half size X-Arapuca device, with a fixed source facing the center, with no cold amplification stage, and discussed in view of the DUNE full size optical cell construction for both the horizontal and the vertical drift configurations of the DUNE TPC design and in view of liquid Argon doping by ppms of Xe. Other particle physics projects adopting Liquid Argon as target or active veto, such as Dark Side and LEGEND or the DUNE Near Detector, may take advantage of this novel wavelength shifting material.